First Report of Clostridium difficile NAP1/027 in a Mexican Hospital - Heimesaat, Markus M.; Camacho Ortiz, Adrián; López Barrera, Daniel; Hernández García, Raúl; Galván de los Santos, Alejandra María; Flores Treviño, Samantha Maribel; Llaca Díaz, Jorge Martín; Maldonado Garza, Héctor Jesús; Bosques Padilla, Francisco Javier; Garza González, Elvira (Public Library of Science, 2015)
Background and Objective Clostridium difficile NAP1/ribotype 027 is associated with severe disease and high mortality rates. Our aim was to determine the prevalence of NAP1/ribotype 027 among C. difficile isolates in a tertiary care hospital, and review the main clinical data. Methods We included 106 stool samples from 106 patients. Samples were tested for A&B toxins and were cultured on CCFA agar. The genes tcdA, tcdB, tcdC, cdtA, and cdtB were amplified using PCR in clinical isolates. The tcdA 3’-end deletion analysis, PCR-ribotyping, and pulsed-field gel electrophoresis (PFGE) were also performed. Stool samples that were positive for culture were tested by the GeneXpert C. difficile assay. Clinical data were collected. Results Thirty-six patients tested positive for A&B toxins; and 22 patients had positive culture for C. difficile, 14 of which tested positive for the A&B toxins and all 22 patients tested positive by the GeneXpert C. difficile assay. Risk factors included an average hospital stay of 16.1 days prior to toxin detection, average antibiotic use for 16.2 days, and a median of 3 antibiotics used. The 30-day crude mortality rate was 8.4%. Six of the 22 patients died, and 3 of those deaths were directly attributed to C. difficile infection. The majority of isolates, 90.9% (20/22), carried genes tcdB, tcdA, cdtA, and cdtB; and these strains carried the corresponding downregulator gene tcdC, with an 18-bp deletion. PFGE was performed on 17 isolates, and one main pattern was observed. Analysis of the ribotyping data showed similar results. Conclusion The above findings represent the clonal spread of C. difficile in our institution, which mainly includes the NAP1/027 strain. This is the first report of C. difficile ribotype NAP1/027 in Mexico